The Use of Journal Writing to Improve High School Students` Writing - Masdianti; Risma Asriani; Titin Suhartini (Institut Parahikma Indonesia, 2021)
The research aimed to find out whether journal writings developed students’ writing skill. The method employed in this research was a pre-experimental design, where a pretest, a treatment and a posttest were given to measure students’ writing skill. The instrument of this research was writing tests which consisted of two guided themes. The population of this research was the ninth-year students of SMP Negeri 18 Makassar in academic year of 2017/2018. The total sample of this research consisted of thirty students. A cluster random sampling technique was used. The data collected was analyzed through descriptive statistical analysis. The results of the paired-sample t-test of this research indicated that there was a slight development of the students’ posttest scores after applying journals in their assignments within six meetings. The students mentioned that the interesting themes made them excited to write. In writing the personal narrative, the students were trained to find the stories they think are best for sharing with others. Therefore, the data analysis tended to show the relation between journal writings and the students’ skill in writing. However, not all students can be easily encouraged to write.